2019
DOI: 10.31557/apjcp.2019.20.8.2551
|View full text |Cite
|
Sign up to set email alerts
|

The Carcinogenic Agent Diethylnitrosamine Induces Early Oxidative Stress, Inflammation and Proliferation in Rat Liver, Stomach and Colon: Protective Effect of Ginger Extract

Abstract: Background:Diethylnitrosamine (DENA), a well-known dietary carcinogen, related to cancer initiation of various organs. The present study investigated the deleterious mechanisms involved in the early destructive changes of DENA in different organs namely, liver, stomach and colon and the potential protective effect of GE against these mechanisms. Methods:Adult male albino rats were assigned into four groups. A normal control group received the vehicle, another group was injected with a single necrogenic dose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 85 publications
(89 reference statements)
5
30
1
Order By: Relevance
“…This observation was supported by a decrease in mRNA levels of inflammatory factors such as IL-6 and IL-8. Further, S-[6]-gingerol was found to reduce both IL-1 β -induced COX2 upregulation and NF- κ B activity [ 63 ]. In another study, 6-gingerol was shown to forestall the increase in inflammatory markers such as myeloperoxidase, NO, and TNF-alpha in the brain, ovaries, and uterus of rats treated with chlorpyrifos.…”
Section: Discussionmentioning
confidence: 99%
“…This observation was supported by a decrease in mRNA levels of inflammatory factors such as IL-6 and IL-8. Further, S-[6]-gingerol was found to reduce both IL-1 β -induced COX2 upregulation and NF- κ B activity [ 63 ]. In another study, 6-gingerol was shown to forestall the increase in inflammatory markers such as myeloperoxidase, NO, and TNF-alpha in the brain, ovaries, and uterus of rats treated with chlorpyrifos.…”
Section: Discussionmentioning
confidence: 99%
“…NDEA stimulates inflammatory cell infiltration (e.g. lymphocytes, neutrophils, eosinophils, and Kupffer cells), pro-inflammatory cytokines, including the IL-1 and IL-6 signaling pathway, as well as oxidative stress and proliferation in the liver, stomach and colon including cyclooxygenase (COX-2) expression in hepatic tissues ( Ding, Wu, Wei, Shu, & Peng, 2017 ; Duan et al, 2014 ; Hebels et al, 2009 ; Mansour et al, 2019 ). Thus, inflammation plays a critical role in carcinogen-induced cancers.…”
Section: Mechanisms Of Pro-tumorigenic Activity By Carcinogensmentioning
confidence: 99%
“…ROS are an important mechanism for tumor promotion and oxidative stress. As a consequence of NDEA-induced oxidative and nitrosative DNA damage ( Klaunig & Kamendulis, 2004 ; Unsal & Belge-Kurutas, 2017 ), inflammatory markers such as IL-1β and TNF-α are significantly elevated in liver, stomach and colon ( Mansour et al, 2019 ). The NDMA-mediated increase in NO production may also contribute to oxidative stress, a factor in the pathophysiology of numerous immune disorders.…”
Section: Mechanisms Of Pro-tumorigenic Activity By Carcinogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding liver tissue of groups treated with compound 4 or 5, the histopathology revealed vacuolar degeneration, most prominent being macro-vesicular in rats treated with compound 4 and less so in rats treated with compound 5. Renal tissue of groups treated with compound 4 and compound 5 showed prominent improvement within both glomeruli and tubules, glomeruli showed average cellularity, tubules showed patent lumina, being lined by low cuboidal epithelium, no vacuolar degeneration, no blood casts and no interstitial congestion [24,25].…”
Section: Histopathology Studymentioning
confidence: 99%